Dependence of Cystatin C and NT-pro-BNP levels on intramyocardial tension of the left ventricle in patients with chronic heart failure - V.V. Syvolap; N.V. Tumanskaya; A.A. Popovych; L.M. Polyschuk (Zaporozhye State Medical University, 2012)
Abstract This article demonstrates the changes of markers of Cystatin C and NT-pro-BNP content in serum of 111 patients with heart failure of ischemic genesis depending on the rate of intramyocardial tension of the left ventricle. It is shown significant increase Cystatin C and NT-pro-BNP levels blood serum taes place as intramyocardial tension of the left ventricle.